Transformasi Pembelajaran dari Luring Menjadi Daring di Sekolah Dasar Pasca-Pandemi COVID-19 - Intan Wahyuni; Elfika Yeni; Cut Kumala Sari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The COVID-19 pandemic triggered a sudden and massive shift from face-to-face (offline) learning to online learning across all levels of education, including elementary schools. This article aims to analyze the transformation process, identify the challenges faced, and examine adaptive strategies implemented by educators during and after the pandemic. Using a qualitative approach through literature review, the study reveals several key issues such as unequal access to technology, limited digital competence among teachers, and the crucial role of parental support at the elementary level. It also explores how blended learning and creative media usage emerged as practical solutions. The findings highlight the need for sustainable digital education models that are inclusive, adaptive, and supportive of students' developmental needs in the post-pandemic era.